An analysis of internationalisation behavior of firms through activities and the case of Turkish firms - (:unkn) unknown (ELSEVIER SCIENCE BV, 2012)
This paper is structured as follows: in the first part we present the internationalisation process theories and arguments including learning process, born global approach, internetisation process and networking which are classified as market focused approaches. The second part presents some general patterns of the internationalisation process of Turkish firms. Our study on how and when Turkish companies began to invest abroad is based on a database consisting of all known manufacturing firms with subsidiaries abroad before the year 2000. This paper also discusses the internationalisation of Turkish firm in light of the internationalization process theory, and focuses on the period from the end of 1980 to 2010. It seems that Turkish firms, in their internationalisation process use their network in addition to learning from existing export markets and market knowledge. It is appearent from the secondary data analysis that companies make use of know-how knowledge resulting in gaining experience in international markets other than relying only on export.
Keywords: Internationalisation process; internationalisation strategy; international market knowledge; Turkish companies; EXPORT BEHAVIOR; ORIENTATION; KNOWLEDGE